LAYANAN KEBUNGHATTAAN DI PERPUSTAKAAN UNIVERSITAS BUNG HATTA - Nanda Yudisman, Septevan (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
This article contains a discussion of the public relations services at the Bung Hatta University Library. The bunghatta service is a service in the library which is the hallmark of the library because it has a collection room related to bunghattaan and BAM. There are several problems with this service, namely the lack of interest in visiting users. This is caused by several factors, namely the lack of human resources on duty at the library, the service room is not well maintained, the lack of available information technology, and the lack of promotion. Several of these causal factors have occurred since the occurrence of the Covid-19 Pandemic until now and librarians still have not found alternative repairs or updates to overcome this problem. This study uses field research methods (Field Research) and descriptive qualitative.